THE PROBLEM OF INSOLVENCY OFFICER’S LEGAL RELATIONS - V. P. Karnaukh (Стратегические решения и риск-менеджмент)
This article is devoted to the various problems which may appear in connection with insolvency officer’s activity, specifically, to the different aspects of insolvency officer’s legal relations, which includes: insolvency officer’s authority certification, insolvency officer’s representation, bank card’s certification by insolvency officer, insolvency officer’s sealing.